Analisis Performa Jaringan Software Defined Networking dengan Algoritma Random Early Detection - Manuputty, Yandri Y; Widiasari, Indrastanti R. (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2024)
In the management of SDN networks, the main challenges faced are traffic congestion and network overload. One of the solutions that has been implemented is the Random Early Detection (RED) algorithm. This research aims to analyze the performance of SDN networks with the implementation of the RED algorithm compared to SDN networks without the use of the RED algorithm. The results of the study show that the use of the RED algorithm (Random Early Detection) in SDN networks has a significant impact on Quality of Service (QoS) parameters, such as packet loss, throughput, and average delay. In high load conditions, there is a controlled increase in packet loss with RED as the number of hosts increases. The average packet loss with RED is 1.57% for 4 hosts, whereas without RED, it is only 1.4%. RED also has a positive impact on throughput, with an average throughput of 243.8 kbps for 4 hosts with RED, while without RED, it only reaches 124.3 kbps. Furthermore, the use of RED reduces the average delay in packet delivery. The average delay with RED is 3.8 ms for 4 hosts, whereas without RED, it reaches 5.92 ms.